Comprehensive agroproductive characterization: A study of the cantons of Manabí – Ecuador - Moreira-Saltos, Juan R. (2024)
This study analyzed agroproductive systems in the cantons of Chone, San Vicente, Sucre, Flavio Alfaro, El Carmen, and Bolívar in Manabí province, Ecuador. A descriptive-exploratory strategy, with no variable manipulation, was utilized in a non-experimental investigation. The sample included 149 residents in the region who submitted demographic information as well as details on their agricultural practices. The findings revealed that agriculture is the most common activity, with more than half of respondents focusing on short-cycle crops, mostly maize, while others focus on perennial crops, including cocoa. Furthermore, cattle raising, particularly for milk, is an important sector in the area. Although to a lesser level, engagement in pig, poultry, and forestry production was noted, all of which contributed to local growth. However, infrastructural issues and a lack of technical innovation were detected in all of these agro-productive activities, which may limit the region's agricultural sector's potential for growth and sustainable development. Keywords: agricultural production systems, food security, local development, crop diversity.